The etiology of clonal mosaicism in human aging and disease - Massaar, Sanne; Sanders, Mathijs A. (Aging and cancer, 2023)
Our DNA is consistently assaulted by a variety of intrinsic and extrinsic mutational factors. Fortunately, DNA repair provides for protective barriers that limit the full manifestation of DNA damage. Yet, DNA repair represents no panacea as DNA damage continuously slips through these erected defenses and materializes as mutation, which can have undesirable consequences as seen for cancer. Acquisition of early driver mutations can engender mutated stem cells with increased cellular fitness resulting in clonal expansion (CE) and increased risk of malignant disease. Tissue clonal mosaicism as observed in the elderly is therefore the natural outcome of continuous driver mutation acquisition in stem cells and their subsequent clonal outgrowth. Hence, a major emerging theme is that CE is an idiosyncrasy of the aging human tissue. This phenomenon can have diverse health consequences that we here divide into three categories: cancer, non‐cancer morbidity, and disease protection. This review outlines current day knowledge on clonal outgrowth, how it relates to health and aging, and how in the framework of DNA repair deficiencies these subjects are consolidated. Our DNA is consistently assaulted by a variety of intrinsic and extrinsic mutational factors. Fortunately, DNA repair provides for protective barriers that limit the full manifestation of DNA damage. Yet, DNA repair represents no panacea as DNA damage continuously slips through these erected defenses and materializes as mutation, which can have undesirable consequences as seen for cancer. Acquisition of early driver mutations can engender mutated stem cells with increased cellular fitness resulting in clonal expansion (CE) and increased risk of malignant disease. Tissue clonal mosaicism as observed in the elderly is therefore the natural outcome of continuous driver mutation acquisition in stem cells and their subsequent clonal outgrowth. Hence, a major emerging theme is that CE is an idiosyncrasy of the aging human tissue. This phenomenon can have diverse health consequences that we here divide into three categories: cancer, non‐cancer morbidity, and disease protection. This review outlines current day knowledge on clonal outgrowth, how it relates to health and aging and how in the framework of DNA repair deficiencies these subjects are consolidated.